DEVELOPING A PROGRAM FOR TEACHING QUANTUM PROGRAMMING TO HIGH SCHOOL STUDENTS IN TURKEY - Sevdanur Genç; Cumali YAŞAR; Hüseyin Türker; Tülay Dargut Güler (Journal of Advancements in Education, 2023)
Quantum physics is the branch of science that studies the behavior of molecules, atoms, subatomic particles and photons, and quantum computers are used to use these subheadings in information communication. In these computers, quantum programming languages and their interfaces have been developed to communicate information. Quantum programming is a software development system that has superior features compared to classical programming and its applications can address very wide areas. In Turkey, the use and dissemination of computer programming languages is included in the curricula of the Ministry of National Education from the 5th grade of primary education. Especially block-based programming is especially applied at all levels of basic education. At the secondary education level, vocational and technical Anatolian Anatolian high schools have an information technology field, where students are taught various programming languages such as Python and C# starting from the 9th grade. In all other secondary education institutions except vocational high schools, students are taught programming languages under the name of computer science courses and thus students are supported in the field of software development. Quantum programming, which entered our lives with the development of today's technology and the second quantum revolution, brings a completely different dimension to the field of software development. At this point, it is predicted that students should be involved in quantum programming at an early age. The aim of this study is to develop a course design for teaching quantum programming to high school students in order to create competent societies that follow new technological developments. ADDIE instructional design model was used in this course design and it is thought that this study will contribute to Turkish literature.
Keywords: 4. Education